2019
DOI: 10.2147/dddt.s218606
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effect of Glutamine Supplementation on Oxidative Stress and Matrix Metalloproteinase 2 and 9 After Exhaustive Exercise</p>

Abstract: BackgroundGlutamine is the most abundant amino acid in plasma and skeletal muscles and an important fuel for immune system cells. It has beneficial anti-inflammatory and antioxidant properties which may be considered as a potentially useful supplement for athletes. The present study was conducted to investigate the effect of glutamine supplementation on oxidative stress and matrix metalloproteinase 2 and 9 after exhaustive exercise in young healthy males.Materials and methodsIn this study, 30 healthy males (su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Thus, the metabolomic analysis was performed, and 3 metabolites, including glutamine, unsaturated acids, UFA [CH = CH], and glucose, were changed after berberine treatment. Glutamine is the most abundant amino acid in the body, with antioxidant and anti-inflammatory properties [31,32]. Numerous studies indicated that oxidative stress and chronic inflammation might have an important effect on the pathophysiology of PCOS [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the metabolomic analysis was performed, and 3 metabolites, including glutamine, unsaturated acids, UFA [CH = CH], and glucose, were changed after berberine treatment. Glutamine is the most abundant amino acid in the body, with antioxidant and anti-inflammatory properties [31,32]. Numerous studies indicated that oxidative stress and chronic inflammation might have an important effect on the pathophysiology of PCOS [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 34 included studies, 19 used a parallel group design [ 48 , 49 , 51 , 52 , 53 , 54 , 55 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ], 3 had three treatment arms [ 52 , 54 , 63 ], and 2 had four treatment arms [ 68 , 74 ]. The remaining 15 studies employed a crossover design [ 8 , 30 , 50 , 56 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ], three of which had three treatment arms [ 50 , 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another study, consuming 1.5 g/kg of glutamine for 7 days prior to running did not affect the post-exercise changes in TAC, glutathione, or MDA (p > 0.05) [48]. In contrast, Nemati et al [67] found that 0.3 g/kg of glutamine for 2 weeks prior to exhaustive exercise significantly increased the systemic TAC (p = 0.01) and glutathione (p = 0.002) and reduced the post-exercise levels of serum MDA (p = 0.04) and hsCRP (p = 0.02).…”
Section: Amino Acid Interventionsmentioning
confidence: 98%
“…Currently, extensive scienti c attention has been given to an important metabolite Gln, which is one of the most abundant amino acid in the human body, such as skeletal muscles, plasma [33] and follicular uid [34]. It has anti-in ammatory and antioxidant functions as well as effects that modulate the heatshock protein response during stress; moreover, as a precursor of glutamate, Gln participates in multiple neurotransmitter metabolic pathways [33,35,36]. In addition, peripheral neurotransmitter NE participates in the control of steroidal secretion from the ovary and follicular development [29].…”
Section: Discussionmentioning
confidence: 99%